Slava geroyam sovetskogo soyuza! Usiliyami partii i pravitel'stva vse chelyuskintsy spaseny! - Leonov, Gennadi Artemovic (1934)
Colour lithograph, mainly blue and grey; icy landscape with flag of Soviet Union; portraits of the aircraft pilots who rescued the SS Cchelyuskin in the Artic Poster in homage of the Soviet steamship SS Chelyuskin, which navigated the Artic until it became icebound; aircraft pilots who rescued the ship crew were decorated as heroes. Original title: Слава героям советского союза! Усилиями партии и правительства все челюскинцы спасены! PO-0130